Entanglements, ontologies, and grinding stones at the medieval site of Handoga (Djibouti) - de Torres Rodríguez, Jorge (2024)
This paper analyses the role and meaning of grinding artefacts in Handoga (Djibouti), a medieval town that flourished between the 13th and 16th centuries in a territory previously occupied by nomadic communities. The technicalmorphological and morphological-functional studies conducted on the sample suggest that the management of tools related to agriculture followed anapproach characterized by minimal care through the different stages of the objects’ lives. This situation, contradictory to what could be expected in a town that had been sedentary for centuries, has been used to reflect on the interrelations between these objects and their users, following Hodder’s concept of entanglement. The analyses conducted on Handoga’s tools point that contrary to what could be expected, some processes such as sedentarization, which are usually conceived as univocal or inevitable can be negotiated or even rejected, and the material-human interactions built around them can also be untangled, if desired.